Виставка промислів і рукоділля 1851 року у Львові - Король, С. (Інститут народознавства НАН України, 2007)
The article considers the unknown page in the history of the Ukrainian applide and decorative art — the Lviv industry and craft exhibition in 1851 and discoveres circumstences of its appearence and organization. This problem has been taken in completed context with the wide process in the westeuropean applide and decorative art both design in the middle of the 19th century.